An Exploration of the Relationship between Leadership, Motivation, Environment, and Performance in Small and Medium Food Distribution Enterprises - Hafni, Layla; Anita, Anita; Vanesa, Setevy; Safari, Surya; Tjahjana, Dominicus Josephus Swanto (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This study aims to determine how much influence leadership, work motivation, and environment have on employee performance at UD. Citra Pekanbaru. The sampling technique used a saturated sample, with the sample taken in the study in the form of all employees at UD. Citra Pekanbaru as many as 42 people, the data taken using the Questionnaire (questionnaire) method. The data analysis technique used is multiple linear regression analysis where the independent variable consists of leadership, work motivation, and environment, and the dependent variable is employee performance. The results showed that partial leadership (X1) had a significant effect on employee performance, work motivation (X2) had a positive and significant effect on employee performance and the environment (X3) had a significant effect on employee performance.